ANALISIS STRUKTUR BAWAH PERMUKAAN DAERAH HARJOSARI KABUPATEN SEMARANG MENGGUNAKAN METODE GEOMAGNET DENGAN PEMODELAN 2D DAN 3D - Mars Widodo; Tony Yulianto; Udi Harmoko; Gatot Yulianto; Sugeng Widada; Yusuf Dewantoro (Youngster Physics Journal, 2016)
Research of analysis subsurface structure in Harjosari Semarang district using geomagnet methods with 2D and 3D modelling. In this study, magnetic data acquisition was carried out in 93 points by using a PPM (Proton Precession Magnetometer) geometrics type of GSM 19T and 2 units geotron magnetometer G5 models to get the values of the total magnetic field. The result of measurement data is processed by the daily variation correction and IGRF correction (International Geomagnetic Reference Field). The corrected data has been used to create total magnetic anomaly contour. The total magnetic anomaly contour has been used to process reduction to plan surface. The result of reduction to plan surface has been used to create a contour upward continuation and then made reduction to the poles. The result of research showed the total magnetic anomaly closure pair of positive and negative indicated a fault zone below the surface. Result of research an incision on the closure pair of positive and negative to determine the subsurface structure of the region by creating a model of 2-dimensional (2D) using software Mag2DC. In 2D modeling result shows that was a fault zone below the surface about 210 to 1000 meters depth. The existence of the fault structure below the surface was estimated as a result of rock shifting from the northeastern area of research. Result of a 3-dimensional (3D) modelling using UBCMag3D software to determine subsurface structures more clearly by including error values, parameter values susceptibility and density models. On the results of the 3D display of subsurface structures found any difference in stark contrast to the susceptibility value at a depth of 225 meters to 1200 meters. The susceptibility value differences suspected presence of fault structures below the surface.